Medical miracle in the Quran - Bazirgan, Muhamad Husain Kassim (2010)
Quran, to the Muslim, is the irrefutable, inimitable Word of Allah(Subhanaho Wa Talah). It was revealed by Allah Almighty, through the instrument of Prophet Muhammad(peace be Upon Him). The Prophet (peace be Upon Him) himself had no role in authoring the Quran, he was merely a human secretary, repeating the dictates of the Divine Creator. The Holy Qur'an is the Holy Book of ISLAM. The verses of the Holy Qur'an were revealed to Prophet Muhammad (peace be Upon Him)by the Angel Jebreel over the period of twenty three years. One or more verses were revealed at a time. The Holy Qur'an is a complete constitution that Allah (SWT) Bestowed on mankind. Its verses give ALLAH's rules and laws for all aspects of life. As well as Quran tells a wide range of scientific phenomena. Concentrating on the medical ones including the human developmental stages, the physiology of the human body, the effect of practicing worships on improving the health, the nutrition aspect as well as controlling diseases, these fact in addition to many others were brought to Prophet Muhammad (peace be Upon Him) since more than 1400 years. The modern science only within the last century proved the reality of these fact to be considered as scientific miracles, from ALLAH.